Determinant of anemia in pregnancy at Polewali Mandar District, South Sulawesi, Indonesia - Sumiyati; Elizabet C. Jusuf; Aminuddin; Muhammad Rachmat (Elsevier, 2021)
Objectives: The study was aimed to determine the influence of the determinant of anemia in pregnancy in the district Polewali Mandar, Indonesia. Methods: This study uses a cross-sectional design analysis. The subject in this study was the third-trimester pregnant mother with a sample amount of 80 people selected using the cluster sampling technique. Results: The majority of this study showed that as much as 93.8% of the third-trimester pregnant women were suffering from anemia, and 6.8% of the third-trimester pregnant women were not subjected to anemia. Based on statistical test results using the Chi-Square test obtained that age (P-value = 0.644), education (P-value = 0.003), economic Status (P-value = 0.138), Antenatal care visit (P-value = 0.584), nutritional Status (P-value = 0.929), parity (P-value = 0.380), Pregnancy distance (P-value = 0.776), consumption of iron tablets (P-value = 0.036) and worm infections (P-value = 0.821). Results showed that two determinants significantly affect anemia in pregnancy, and seven determinants did not significantly affect anemia in pregnancy Regency of Polewali Mandar. Conclusion: A significantly related determinant in the study is the education and consumption of iron tablets.